Air quality in the context of its monitoring in Central and Eastern Europe in 2010-2020 - Magdalena Proczek; Małgorzata Beata Dziembała (Journal of Modern Science)
Objectives The purpose of this article is to discuss the issue of air quality monitoring by means of Sustainable Development Indicators (SDIs), and to present the changes in Central and Eastern European (CEE) countries that have taken place in this respect.